Peran Sales Marketing Department Dalam Penjualanmice Package Pada Hotel The Sintesa Jimbaran Bali - Napitupulu, Binur Pretty (Politeknik Pariwisata Medan, 2024)
Bali Island is an area with a high percentage of tourist visits and MICE activities, especially those located in BTDC Nusa Dua Bali, this has resulted in many investors, both local and foreign, to establish hotels, both budget hotels or starred hotels. With this hotel business competition, of course, it requires a reliable marketing or sales marketing team. Of several hotels in Bali, according to the author, Hotel The Sintesa Jimbaran Bali has a good existence in terms of increasing occupancy. MICE tourists generally have a longer length of stay, because they participate in pre- and post-tour activities with various programs such as ladies and children programs so that overall tourist spending is greater. In addition, MICE tourists have a relatively higher level of immunity to various unclear issues in a country so that they are not easily able to cancel their visits. In addition, MICE events provide direct benefits to the community's economy such as accommodation, culinary businesses, souvenirs, guides, and local transportation. The advantages of the MICE industry include attracting tourists in large numbers, longer length of stay, or short ones which are also called temporary holidays.